Raising Awareness of the Impact of Stunting on Toddler Development Through Parental Education - Yanti, Eka Safitri; Imami, Retno; Arica, Arica (LP2M INSURI Ponorogo, 2024)
In 2023, the prevalence of stunting in Indonesia remains at 21.5%, showing only a marginal decrease of 0.1% from the previous year and still exceeding the WHO standard of 20%. Stunting adversely affects children, leading to impaired physical and cognitive development, increased risk of developmental disorders, and a higher likelihood of metabolic diseases in adulthood.This study utilized a multi-stage approach: data and area analysis, educational and developmental screening, and evaluation. Participants included 44 parents with their toddlers, 5 cadres, and 3 village officials. Knowledge among participants improved significantly, with 76% demonstrating enhanced understanding. Statistical analysis revealed a significant increase in knowledge post-intervention (p=0.000). Developmental assessments showed that 11% of toddlers were classified as